Assessing Blockchain Technology application for freight booking business: a case study from Technology Acceptance Model perspective. (22nd September 2020) - Tan, Wee Kwan Albert; Sundarakani, Balan
Abstract : Purpose: The purpose of this study is to develop a framework for a freight consolidation company to adopt blockchain for the shipping community. Our research critically examine the challenges faced by a global shipping company that offer freight consolidation businesses and explore the use of Blockchain technology to enhance the competitiveness and sustainability of freight booking operations. Design/methodology/approach: This paper is a case study, ECU Worldwide, with focus on transforming their operations using blockchain technology for the freight booking industry. As the case is explorative in nature, the research aim to unearth the complex blockchain adoption phenomenon in the industry as the technology is very nascent at present. The research is primarily grounded on Technology Acceptance Model (TAM) theory. Findings: The research finds that blockchain technology supports solving many issues and inefficiencies of global shipping operations but there are some barriers that they need to overcome. The research provides a framework and recommendations for global company to consider when considering Blockchain technology for implementation. Our research finding shows that smart contracts can be set up at critical points along with the shipment route namely the storage, customs, carrier, transporters and consignee stage to ensure greater security and transparency. Research limitations/implications: The research provides recommendations to key stakeholders involved in freight forwarding segment of logistics industry while adopting blockchain technology. Apart from the methodological limitation of the research, the research is limited to Singapore in terms of geographical coverage. Practical implications: The drivers and barriers identified in the study can give practitioners insight of using blockchain for the industry. The proposed framework can assist companies in the shipping industry to prepare themselves to adopt blockchain for the community. Originality/value: This case study is the first of its kind to examine the use of blockchain to explore the adoption in logistics Industry in Singapore and perhaps worldwide.